Preseptal Cellulitis In A 54-Year-Old Woman With Uncontrolled Diabetes Mellitus: A Case Report - Adam Primadona Satari; Bernadetha Kusuma Kris Firmantya Tei Seran; Oktarina Nila Juwita (International Journal Labs, 2025)
Preseptal cellulitis is a skin infection around the eye that can originate from various sources such as sinusitis or trauma. This study explores the case of a 54-year-old patient with uncontrolled type 2 diabetes who presented with preseptal cellulitis. The patient complained of redness and pain around the left eye, with a history of fever and swelling for three days prior. Physical examination revealed hyperemic edema on the upper eyelid of the left eye with positive tenderness. Additionally, the patient had a history of uncontrolled type 2 diabetes. CT-scan imaging of the orbit and paranasal sinuses revealed hyperpigmentation on the left extraocular bulb, opacity in the right maxillary sinus with a polyp impression, and a hyperdense lesion in the right maxillary sinus with evidence of hyperostosis of the right maxillary bone. Laboratory results showed hyperglycemia, leukocytosis, uremia, and increased creatinine. The established diagnosis was preseptal cellulitis with potential complications. The discussion involves clinical aspects and management of preseptal cellulitis, including orbital anatomy, infection spread, diagnosis, and treatment. Patient management included the administration of antibiotics, anti-inflammatory drugs, and glycemic control. This study emphasizes the importance of research into the relationship between type 2 diabetes and preseptal cellulitis for a better understanding of risk factors and optimal management. In conclusion, this research provides in-depth insights into the complexity and risks of preseptal cellulitis in patients with uncontrolled type 2 diabetes and underscores the need for proper management to reduce complications in this condition.